2023
DOI: 10.3390/agriculture13010222
|View full text |Cite
|
Sign up to set email alerts
|

Decomposition and Nitrogen Release Rates of Foliar Litter from Single and Mixed Agroforestry Species under Field Conditions

Abstract: Decomposition and N release pattern from the leaves of three shrubs species were studied under field conditions. Leaves of Leucaena leucocephala (Lam.), Guazuma ulmifolia (Lam.) and Moringa oleifera (Lam.) and two mixtures, Leucaena + Moringa and Leucaena + Guazuma, in a complete randomized block design, were studied during the dry and wet seasons. Litterbags were randomly distributed in each experimental block and placed on the soil surface, and residues were recovered after 2, 4, 8, and 16 weeks. Double expo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 35 publications
0
1
0
Order By: Relevance
“…It is important to note that the impact of agroforestry systems on OC content in tropical soils can vary depending on various factors, such as tree species, management practices, climate, and soil type. For instance, studies have shown that the type of tree species and their litter quality can significantly influence the rate of OC accumulation in soil, with leguminous trees generally having a greater impact due to their higherquality litter and nitrogen-fixing abilities [133,134]. In addition, management practices, such as pruning, mulching, and intercropping, can also affect the amount and quality of litterfall, nutrient cycling, and soil physical properties, which can, in turn, influence the OC content in soil [129,135].…”
Section: Impact Of Agroforestry Systems On Soil Physical Properties N...mentioning
confidence: 99%
“…It is important to note that the impact of agroforestry systems on OC content in tropical soils can vary depending on various factors, such as tree species, management practices, climate, and soil type. For instance, studies have shown that the type of tree species and their litter quality can significantly influence the rate of OC accumulation in soil, with leguminous trees generally having a greater impact due to their higherquality litter and nitrogen-fixing abilities [133,134]. In addition, management practices, such as pruning, mulching, and intercropping, can also affect the amount and quality of litterfall, nutrient cycling, and soil physical properties, which can, in turn, influence the OC content in soil [129,135].…”
Section: Impact Of Agroforestry Systems On Soil Physical Properties N...mentioning
confidence: 99%